ANALISA KANDUNGAN FORMALIN PADA PRODUK TAHU PUTIH DI KECAMATAN WONGSOREJO: Analysis of Formalin Content in White Tofu Products in Wongsorejo - Ahmad Bilhaqqi Nazal, Rosiana Ulfa, Restiani Sih Harsanti (Program Studi Teknologi Hasil Pertanian Universitas PGRI Banyuwangi, 2022)
Tofu is one source of protein from white soybeans by finely milling, boiling, and printing. The shelf life of tofu is very limited, under normal conditions (room temperature) the shelf life is on average 1-2 days, if more than this limit the taste of tofu will turn sour and give rise to a rotten aroma so it is not suitable for consumption. This makes foods such as tofu often added with chemicals or natural ingredients to make them last longer. One of the chemicals that is dangerous and often used is formalin, so there is a need for research on the content of formaldehyde in white tofu, especially in Wongsorejo District because white tofu is one of the foods that are often consumed by the community. This research was initiated by collecting tofu samples from four tofu factories in Wongsorejo District, namely Wongsorejo Village. The test was carried out qualitatively by using the Formalin Test Kit method. Based on the physical test and qualitative formalin test conducted on the four tofu samples taken from factories in the Districts of Wongsorejo, Sumberkencono, Bajulmati, and Sidodadi, it was found that all samples did not contain formalin.